2015
DOI: 10.1111/jnc.13441
|View full text |Cite
|
Sign up to set email alerts
|

Activation of microglial Toll‐like receptor 3 promotes neuronal survival against cerebral ischemia

Abstract: Emerging experimental evidence suggests that activation of Toll-like receptor 3 (TLR3) by its agonist polyinosinic polycytidylic acid (poly-ICLC) protects neurons against cerebral ischemia, but the underlying mechanisms remain largely unknown. In the brain, TLR3 is mostly expressed in glial cells. Therefore, we assess the hypothesis that TLR3 activation in microglia is required for neuroprotection against ischemia. After transient focal cerebral ischemia, microglia/macrophages (MMs) demonstrate a significant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Bsibsi et al's work showed that inflammation-induced TLR-3 activation triggers a neuroprotective response rather than a proinflammatory response in human astrocytes [ 59 ]. Furthermore, Jeong et al's work showed that polyinosinic poly-cytidylic acid- (poly(I:C)-) induced activation of TLR3 might favor the survival of microglia after cerebral ischemia, suggesting the neuroprotective role of TLR3 [ 60 ]. Controversially, the activation of TLR might also create a degenerative effect in neuron cells; for example, Chintala et al's work showed that poly(I:C)-induced TLR3 activation upregulated the protein level of MAPK JNK3 and promoted the degeneration of RGCs in mouse eye [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bsibsi et al's work showed that inflammation-induced TLR-3 activation triggers a neuroprotective response rather than a proinflammatory response in human astrocytes [ 59 ]. Furthermore, Jeong et al's work showed that polyinosinic poly-cytidylic acid- (poly(I:C)-) induced activation of TLR3 might favor the survival of microglia after cerebral ischemia, suggesting the neuroprotective role of TLR3 [ 60 ]. Controversially, the activation of TLR might also create a degenerative effect in neuron cells; for example, Chintala et al's work showed that poly(I:C)-induced TLR3 activation upregulated the protein level of MAPK JNK3 and promoted the degeneration of RGCs in mouse eye [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Gao et al's work showed that poly(I:C)-induced TLR3 evoked an inflammatory response and cell death both in murine photoreceptor 661W cells and an in vivo model [ 62 ]. Therefore, the role of TLR in prosurvival or pro-cell death of neuron cells may depend on the types [ 55 ] of stimuli, the level [ 60 ] of stimuli, and the downstream of TLR signaling [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…; Jeong et al . ) and conversion between different phenotypes seems now critical next step to clarify the factors that initiate or promote such changes. Thus, inhibition of microglia and T‐cell activation by calpain inhibitor as a therapeutic agent may block neuron death and axonal damage to reduce progression of the degenerative process.…”
Section: Discussionmentioning
confidence: 99%
“…An emerging proof-of-concept studies [ 133 ] provided that a TLR3 ligand, which consists of carboxymethylcellulose, polyinosinic-polycytidylic acid, and poly-L-lysine double-stranded RNA (named poly-ICLC) working as an activation of TLR3 in microglia is also neuroprotective. After focal cerebral ischemia, as well as OGD, TLR3 and IL-6 were found downregulated in microglia/macrophage.…”
Section: Potential Medications or Compounds Acting On Tlrs To Promotementioning
confidence: 99%